Dual Inoculation of Rhizobium and Arbuscular Mycorrhizal Fungi Increases Soil-Total Nitrogen, Available Phosphorus, and Yield of Soybean in Vertisols - Lily F Ishaq; Ingracia J. A. Manehat; Anthonius S. J. Adu Tae; Yoke I. Benggu (Postgraduate, University of Mataram, 2023)
Soybean is a protein source food crop with high economic value. So far, national production has not been able to meet domestic demand resulting in continuing import of soybean. The use of rhizobium and arbuscular mycorrhizal fungi (AMF) as biological fertilizers could be an alternative to increase soybean production. The research aimed to investigate the effect of dual inoculation of rhizobium and arbuscular mycorrhizal fungi (AMF) on root nodules formation, AMF development, total-N and available P of Vertisols, and yield of soybean. This study was designed in a completely randomized design) with 4 treatments namely no inoculation (R0), rhizobium inoculation (R1), AMF inoculation (R2), and dual inoculation of rhizobium and AMF (R3), with four replications. The variables observed were the number of effective root nodules, AMF spore density, AMF colonization, soil total-N, available P, plant height, number of pods, and seed weight. The results showed that dual inoculation of rhizobium and AMF had a better effect on the number of effective root nodules, AMF spore density, AMF colonization, soil total- N, available P, plant height, number of pods, and seed weight compared to the single inoculation and un-inoculated treatments